Predictors of Subsequent Injury After Anterior Cruciate Ligament Reconstruction in Children and Adolescents. Issue 7 (21st July 2017) - Dekker, Travis John; Godin, Jonathan Alexander; Dale, Kevin; Garrett, William E.; Taylor, Dean C.; Riboh, Jonathan Charles
Objectives: Anterior cruciate ligament (ACL) graft failure and contralateral ACL tears are more frequent in children/adolescents than adults. These re-injuries result in significant time lost from sport, and may contribute to worse long-term outcomes and post-traumatic osteoarthritis. The reasons for higher subsequent injury rates in this unique population are incompletely understood. Methods: We analyzed a single center continuous cohort of patients under the age of eighteen years. Subjects underwent primary ACL reconstruction between 2006 and 2014 with minimum 2-year follow up. Age, sex, graft type, duration of physical therapy, time to return to sport, and length of follow-up were evaluated using multivariable logistic regression modeling to assess their contribution to the risk of subsequent ACL injury. Results: A total of 109 subjects met all study inclusion/exclusion criteria. Eighty-two subjects (75%) had follow-up data and were included in the final analysis. Mean age was 14 +/- 1.9 years (range 8 - 17 years). Mean follow-up was 47.7 +/- 15.6 months (range 28 - 91 months). Seventeen patients (20.7%) sustained an ACL graft rupture, eleven patients (13.4%) sustained a contralateral ACL tear, and one patient (1.2%) sustained both. The combined subsequent injury incidence was 35.4% (29 of 82 subjects). The odds of subsequent ACL injury decreased by 0.29 for every yearly increase in age (OR 0.71, 95% CI 0.53 - 0.92, p = 0.008), and decreased by 0.16 for every monthly increase in time to return to sport (OR 0.84, 95% CI 0.69 - 0.99, p = 0.048). Sex, graft type, duration of physical therapy, sport, and length of follow up did not have a statistically significant impact on the rate of subsequent ACL injury (p > 0.05). Conclusion: Subsequent ACL injuries (ipsilateral or contralateral) are common after primary ACL reconstruction in children and adolescents (combined incidence 35%). Within this high-risk population, younger age and an earlier return to sport portend a higher risk of a second injury.